Quasi-Vertical GaN Schottky Barrier Diode on Silicon Substrate With 1010 High On/Off Current Ratio and Low Specific On-Resistance - Y. Li; M. Wang; R. Yin; J. Zhang; M. Tao; B. Xie; Hao, Y.; Yang, X.; Wen, C.P.; B. Shen (IEEE Electron Device Letters, 2020)
In this letter, we report a quasi-vertical GaN Schottky barrier diode (SBD) fabricated on a hetero-epitaxial layer on silicon with low dislocation density and high carrier mobility. The reduction of dislocation is realized by inserting a thin layer with high density of Ga vacancies to promote the dislocation bending. The dislocation density is $1.6× 10^8$ cm?2 with a GaN drift layer thickness of $4.5 μ \textm$ . The fabricated prototype GaN SBD delivers a high on/off current ratio of $10^10$ , a high forward current density of 1.6 kA/cm2@3 V, a low specific on-resistance of 1.1 $\textmØmega · \text cm^2$ , and a low ideality factor of 1.23.
Keywords: dislocation bending; GaN on Si; Schottky barrier diode; vertical structure